Implementation Of The Flight Information Region Boundary Adjustment Agreement Between Indonesia And Singapore - Salsa Nur Ramadhani Hermandasari; Herlita Eryke (UNIVERSITAS PAKUAN, 2026)
Flight Information Region (FIR) boundary adjustment agreement which was agreed upon by the Indonesian Government with the Singapore Government on January 25 2022, which was later ratified through Presidential Decree No. 109 of 2022, is the result of Indonesia's long struggle. In the implementation of the FIR boundary adjustment agreement, issues regarding Indonesia's sovereignty and the substance of the agreement are not in accordance with Indonesian national regulations, such as Article 2 of the FIR adjustment agreement, Indonesia is obliged to delegate management of Riau air to Singapore's FIR and Article 7 which states that the duration of this agreement is valid for 25 years. . This is not in line with the mandate of the Aviation Law which states that all flight navigation services managed by other countries must be completely taken over by Indonesia by 2024. So it is necessary to conduct research on the Implementation of the FIR Boundary Adjustment Agreement between Indonesia and Singapore. With analytical material based on the efforts of the Indonesian Government in resolving the Riau FIR problem and implementing the Indonesian FIR agreement with Singapore which was agreed upon by both parties. This research uses a juridical-normative legal research method with a historical approach, a statutory approach and a conceptual approach. The research results show that First, there is a long history of the Indonesian Government's efforts to take over air sovereignty and FIR management in the Riau Islands airspace. Second, the implementation of the FIR boundary adjustment agreement between Indonesia and Singapore has been implemented, but the Indonesian Government needs to re-evaluate the substance of the FIR Agreement. Keywords : Management, FIR, Agreements, Indonesia, Singapore, Air Sovereignty, Air Space, Flight Information Region, ICAO, International Aviation Law.